Introduction Spectral clustering and functional connectivity analysis of low-frequency fluctuations in fMRI data reveal a distinct separation between the superior temporal sulcus and the superior temporal gyrus - Lohmann, G; Obleser, J; Friederici, A; Turner, R (NeuroImage (Orlando, Fla.), 2009)
A subsequent regression analysis revealed distinctive correlational patterns associated with this subdivision whose interpretation will be the subject of future research.